Dynamical downscaling of daily precipitation over the Iberian Peninsula: a spatial resolution analysis for present and future climate conditions - Sánchez, Enrique; Gaertner, Miguel Angel; Gallardo, Clemente (Física de la Tierra, 2010)
The analysis of daily precipitation over the Iberian Peninsula as modelled by a global climate model (GCM) and a regional climate model (RCM) forced by the GCM, at two resolutions for present climate and A2 scenario of greenhouse gases emissions for the end of 21st century is presented. The spatial structure of total annual precipitation, with a maximum in the northwest of the region and a minimum in the southeast is described by both the GCM and the RCMs, although the GCM is not able to reproduce neither the magnitude of both extremes, nor other more local characteristics, such as the ones related to the complex orography of the Iberian Peninsula mountain chains, or coastal features. Important differences in the spatial structure are also seen in the number of days of precipitation. For climate change conditions, the GCM and the RCMs show a general decrease in the total precipitation and in the number of rainy days.
Keywords: Precipitation; Dynamical downscaling; Climatic change; Regional climate models